Kemampuan Berpikir Tingkat Tinggi Berbasis Teks Bacaan Mata Pelajaran Bahasa Indonesia Siswa Kelas VIII SMP Negeri 2 Polut Takalar - Atiqah, Ramdani; Sultan, Sultan; Sakaria, Sakaria (TITIK DUA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2024)
This study aims to describe students' ability to analyze, evaluate, and create in reading texts of Indonesian language subjects of class VIII students of SMP Negeri 2 Polut Takalar. This research is quantitative descriptive research. The data for this study were obtained from the test results of students' higher-order thinking skills using text-based HOTS (Higher Order Thinking Skills) questions. The data was analyzed using descriptive quantitative methods. The results showed that students' reading text-based higher-order thinking skills at the analyzing level obtained an average score of 55% in the moderate category. At the level of evaluation, students obtained an average score of 59.10%, which is a sufficient category. At the level of creating, students obtained an average score of 48.18% in the low category. Thus, students' higher-order thinking skills are still weak and need to be improved.